GE_GERICHTE A/2429/2020 vom 5. Dezember 2022 - GE Cour de justice (2022)
AUTORISATION DE SÉJOUR;RENVOI(DROIT DES ÉTRANGERS);RESPECT DE LA VIE PRIVÉE | LEI.30.al1.letb; LEI.58a.al1; LEI.96; OASA.31; CEDH.8